Psychiatric Morbidity Among Dermatological Patients Attending a Tertiary Care Hospital in Central India - Divyani Aharwal; Richa Changulani; Akshat Pathak; Durgesh Shukla (Medsci Publications, 2023)
Background: Aim of the study was to estimate prevalence of depression, anxiety and stress among a large sample of out patients, affected with wider variety of skin problems and also to investigate its association with socio demographic and clinical characteristics so as to recommend for interventions to improve quality of care, in patients attending dermatology OPD. Material and Methods: Present hospital based cross-sectional study was conducted among 300 patients attending the dermatology OPD. Frequency, Percentage, Odds ratio (OR) were calculated. Chi square test and Logistic regression was applied. P value < 0.05 was considered as statistically significant. Results: Average age of the participants was 35.5±9.4 years. In the present study 29.67% patients were having at least one of the psychiatric morbidities. Among all the patients 28.7% were having the anxiety; 17.33% were having depression; 9.7% were having the stress. In multivariate analysis Females were observed to have higher risk for anxiety; depression and stress i.e. [OR: 7.54; 95% CI: 3.22-17.63]; [OR: 3.05; 95% CI: 1.75-5.34]; [OR: 14.61; 95% CI: 3.35-63.65] respectively. Conclusion: Female's gender; itching problem and dermatitis need a special concern to reduce the psychiatric morbidity. The high prevalence indicates the need for the psycho-social care of the dermatology patients.